Identifying a sufficient core group for trachoma transmission. - Thomas M Lietman; Michael S Deiner; Catherine E Oldenburg; Scott D Nash; Jeremy D Keenan; Travis C Porco (Public Library of Science (PLoS), 2018)
BACKGROUND:In many infectious diseases, a core group of individuals plays a disproportionate role in transmission. If these individuals were effectively prevented from transmitting infection, for example with a perfect vaccine, then the disease would disappear in the remainder of the community. No vaccine has yet proven effective against the ocular strains of chlamydia that cause trachoma. However, repeated treatment with oral azithromycin may be able to prevent individuals from effectively transmitting trachoma. METHODOLOGY/PRINCIPAL FINDINGS:Here we assess several methods for identifying a core group for trachoma, assuming varying degrees of knowledge about the transmission process. We determine the minimal core group from a completely specified model, fitted to results from a large Ethiopian trial. We compare this benchmark to a core group that could actually be identified from information available to trachoma programs. For example, determined from the rate of return of infection in a community after mass treatments, or from the equilibrium prevalence of infection. CONCLUSIONS/SIGNIFICANCE:Sufficient groups are relatively easy for programs to identify, but will likely be larger than the theoretical minimum.